IDENTIFICATION OF METHICILLIN RESISTANT STAPHYLOCOCCUS AUREUS (MRSA) BY A RAPID PCR TECHNIQUE - Irayyif, Sajjad Mohsin; Kumar, R.senthil; Malla, Sudhakar (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Methicillin-resistantÂ Staphylococcus aureusÂ (MRSA) is one of the most important causes of hospital infections worldwide. High-level resistance to methicillin is caused by theÂ mecAÂ gene, which encodes an alternative penicillin-binding protein, PBP2a.Â Staphylococcus aureus is an important cause of bloodstream infections and a leading cause of severe health careâ€“associated infections. Laboratory diagnostics S. aureus is a Gram positive, catalase positive aerobic or anaerobic coccus showing hemolytic and large yellow colonies. Staphylococcus aureusÂ strains resistant to methicillin and many other antibiotics are major causes of nosocomial infections worldwide. It is of great necessity to check for those genes and check for the potential to clone partial or major fragments into vectors, which can be a potential candidate for DNA vaccines. Novel methods are being developed for the production of antibodies to specific antigens and thus helping in the process of development of protein based vaccines. mecA (Methicillin resistant) gene was isolated and ligated into pTZ57R/T cloning vector. The ligated product was then cloned into DH5Î± strain and allowed to propagate. The plasmids thus cloned were purified and later expressed for the gene of interest in an expression vector. The proteins specific to the gene of interest was then isolated and purified. This proteins purified can in turn be used for protein based vaccines. Key words: Staphylococcus, MRSA, mecA, Cloning.